Antibacterial Potency Test of Suruhan Leaf Ethanol Extract (Peperomia pellucida (L.) Kunth) Against Streptococcus mutans Growth - Amalia; K., Trisnawaty; Anton (Sriwijaya Journal of Dentistry, 2024)
Introduction: One of the pathogenic bacteria that causes dental caries was Streptococcus mutans. The use of antibacterial agents such as chlorhexidine was the gold standard for eliminating Streptococcus mutans but can cause side effects if used long term. Traditional medicine is still used as an alternative by Indonesian people to reduce the side effects of chemical drugs. Suruhan leaves were wild plants that contain antibacterial compounds in the form of alkaloids, flavonoids, saponins, tannins, and phenols which can inhibit bacterial growth. Purpose: This study aims to determine the antibacterial potency of suruhan leaves extract against the growth of Streptococcus mutans bacteria. Methods: This study was an in vitro laboratory experimental study. The treatment group consisted of ethanol extract of suruhan leaves in concentrations of 5%, 10%, 15%, 25%, and 50%. The control group consisted of 0.2% chlorhexidine as positive control and distilled water as negative control. Antibacterial activity test used the disc diffusion method. The inhibition zone values were measured then analyzed using statistical one-way ANOVA and post-hoc Tukey tests. Results: The largest mean inhibition zone of ethanol extract of suruhan leaves formed was 16.47 mm at a concentration of 50%, whereas at a concentration of 5%, it had no antibacterial activity. Conclusion: Ethanol extract of suruhan leaves (Peperomia pellucida (L.) Kunth) concentrations of 10%, 15%, 25%, and 50% had antibacterial activity against Streptococcus mutans.